Food Waste and Quality of Life in Elderly Populations Living in Retirement Living Communities. Issue 1 (2nd January 2019) - McAdams, Bruce; von Massow, Mike; Gallant, Monica
ABSTRACT: Food waste is an increasingly important issue in all food-service establishments, including retirement living communities. With residents of these communities having faced food insecurity as children and young adults, they have unique and very strong feelings regarding this issue. We interviewed 16 Canadian residents and used manifest content analysis to gain an understanding of how their experiences, behaviors, and feelings toward food waste may impact their quality of life. The results of this study may have implications for how retirement living communities approach their food-service operations.